Galería de arte en Chapinero (2017)
This project seeks to generate new spatial and physical relationships in a city node which is problematic today. Through strategies of implementation, an understanding of the city and its dynamics, an Art Gallery is projected that responds to the cultural needs of the Chapinero sector.